CFD modeling of the underwash effect of military helmets as a possible mechanism for blast-induced traumatic brain injury. Issue 1 (2nd January 2017) - Sarvghad-Moghaddam, Hesam; Rezaei, Asghar; Ziejewski, Mariusz; Karami, Ghodrat
Abstract: Underwash occurs as the incoming shockwaves enter the helmet subspace and develop a high pressure region at the opposite side of the head. The mechanism leading to the underwash is yet not well understood. To investigate this effect, the turbulent, supersonic flow of compressible air approaching the head–helmet assembly from different directions was studied through computational fluid dynamics simulations. The effects of different incident overpressures and helmet gap size on the underwash incidence were further evaluated. The backflow-induced pressure from the air traveling outside of the helmet on the outflow from the helmet, as well as the momentum change in the backside curve of the helmet were postulated as the main reasons for this effect. Side shockwaves predicted the highest underwash overpressures. The increase rate of the underwash reduced with increasing the incident shockwave intensity.